Latin American science, technology, and society: a historical and reflexive approach1. Issue 1 (1st January 2018) - Kreimer, Pablo; Vessuri, Hebe
ABSTRACT: The paper deals with the emergence and development the STS field in Latin America, from the sixties on. After an introductory section containing some considerations on the maturation of and approaches to STS in the region, the paper delves into cognitive, institutional, political and social dimensions of the development of this field. It gives then some background, mentioning policies as drivers of knowledge generation, the institutionalization of social studies of science and technology, and STS training. An individual section deals with journals and congresses as spaces for interaction. A chronology of the STS field's development in Latin America is followed by a brief examination of the role of the STS field in contemporary Latin America. It is argued that researchers belonging to this community are in a good position to critically analyze the current relations between science and society, to assist decision-makers and help the public understand the implications of present-day technoscientific change, as well as to support the development of fairer, more equitable solutions to combat the challenges of today's changing world. It goes without saying that, far from having reached maturity, this is a space in a permanent state of construction.